2013
DOI: 10.12691/ajbr-1-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Rytmonorm-Induced Cytogenetic and Testicular Damage in Albino Rats: The Protective Effect of Grapefruit Juice

Abstract: The present work studied the cytogenetic and testicular damage induced by the antiarrhythmic drug rytmonorm (RT) and the protective role of grapefruit juice in albino rats. Treating rats with RT (13.5mg/Kg bodyweight) for five weeks caused a significant increase in the percentage of chromosomal aberrations either structural or numerical and decrease the mitotic index. Using comet assays, RT caused DNA fragmentation in the lymphocytes. Testis of RT treated rats showed many histopathological and morphometric alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our results show atenolol treatment did not affect the gonadosomatic index (GSI) significantly and this results reinforced with (Lin et al, 2015). A significant decrease in sperm aviability was detected in group T1 after 56 days of treatment with atenolol may be due to oxidative insult which effect on sperm DNA and male fertility and could be effect on spermatogenisis and steroid biosynthesis of Leydig cells (Sakr et al, 2013) or may be due to the effect of atenolol on concentration of testosterone (Khan et al, 2004) promote spermatogenesis and maintenance of sperm production (Pineda et al, 2003). This may be attributed to the antioxidant effect of vitamin E which is responsible for its protective effect against oxidative stress, so spermatozoa are protected by antioxidant properties of vitamin E, which removed free radical and improve the sperm viability and gonadosomatic index (GSI) (Momeni et al, 2009).…”
Section: Gonadosomatic Index (Gsi) and Sperm Viability (Live Sperms Psupporting
confidence: 66%
See 2 more Smart Citations
“…Our results show atenolol treatment did not affect the gonadosomatic index (GSI) significantly and this results reinforced with (Lin et al, 2015). A significant decrease in sperm aviability was detected in group T1 after 56 days of treatment with atenolol may be due to oxidative insult which effect on sperm DNA and male fertility and could be effect on spermatogenisis and steroid biosynthesis of Leydig cells (Sakr et al, 2013) or may be due to the effect of atenolol on concentration of testosterone (Khan et al, 2004) promote spermatogenesis and maintenance of sperm production (Pineda et al, 2003). This may be attributed to the antioxidant effect of vitamin E which is responsible for its protective effect against oxidative stress, so spermatozoa are protected by antioxidant properties of vitamin E, which removed free radical and improve the sperm viability and gonadosomatic index (GSI) (Momeni et al, 2009).…”
Section: Gonadosomatic Index (Gsi) and Sperm Viability (Live Sperms Psupporting
confidence: 66%
“…Other study (Sakr et al, 2013) showed that animal given rytmonorm for five weeks showed an increase in the mean number of structural chromosomal aberration, also antihypertensive drug atenolol was found to induce chromosom loss. In addition animal group that treated with atenolol plus vitamin E shows there is less sperm DNA damage due to that vitamin E ameliorate the side effect of atenolol on sperm DNA and allows free radicals to abstract a hydrogen atom from the antioxidant molecule rather than from polyunsaturated fatty acids, thus breaking the chain of free radical reactions, the resulting antioxidant radicals being a relatively unreactive species (Aldana et al, 2001).…”
Section: Detection Of Dna Damage By Agarose Gel Electrophoresisand Anmentioning
confidence: 89%
See 1 more Smart Citation
“…Group II: Rats were orally administered with grapefruit juice (Citrus paradise) at a dose level of 27 ml/kg body weight daily for 6 weeks [14]. Grapefruit (Citrus paradise) used in the work was purchased from local markets in Jeddah…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…[14] reported that grapefruit prevents cytogenetic and testicular damage induced by rytmonorm in rats. The objective of this work is to study the effect of grapefruit in aluminum hepatotoxicity in albino rats.…”
Section: Introductionmentioning
confidence: 99%